Single institution and statewide performance of ultrasound in diagnosing appendicitis in pregnancy. (April 2015) - Drake, Frederick T.; Kotagal, Meera; Simmons, LaVone E.; Parr, Zoe; Dighe, Manjiri K.; Flum, David R.
Abstract Objective: Assess the performance of ultrasound (US) in pregnant patients presenting with acute abdominal pain concerning for appendicitis. Methods: Descriptive analysis of pregnant patients who underwent an US for acute abdominal pain over a 6-year period using data from a statewide quality improvement collaborative and a single center. Results: Statewide, 131 pregnant patients underwent an appendectomy and 85% had an US. In our single-center case series, 49 pregnant patients underwent an US for acute abdominal pain and four patients had appendicitis (8%). Of those, three were definitively diagnosed with US. The appendix was visualized by US in five patients (3 appendicitis/2 normal). Mean gestational age was 11 weeks for visualization of the appendix versus 20 weeks for non-visualization (p < 0.001). Concordance between US and pathology was similar statewide and at our institution (43%). Conclusions: US appears to play a central role in the evaluation of appendicitis in pregnant women, especially in the first trimester, and often contributes to definitive disposition. US performed less well in excluding appendicitis; however, in certain clinical settings, providers appeared to trust US findings. From these results, we developed a multidisciplinary imaging pathway for pregnant patients who present with acute abdominal pain concerning for appendicitis.